A prospective study of smoking during pregnancy and SIDS. Issue 3 (1st September 2000) - Wisborg, Kirsten; Kesmodel, Ulrik; Henriksen, Tine Brink; Olsen, Sjurdur Frodi; Secher, Niels Jørgen
Abstract : AIMS: To study the association between smoking during pregnancy and sudden infant death syndrome (SIDS) using prospectively collected data, making it possible to account for a number of potential confounders. DESIGN: Prospective follow up study (n = 24 986). RESULTS: The overall rate of SIDS was 0.80 per 1000 live births (n = 20). Children of smokers had more than three times the risk of SIDS compared with children of non-smokers (OR = 3.5; 95% CI 1.4–8.7), and the risk of SIDS increased with the number of cigarettes smoked per day (p < 0.05). Adjustment for parity, alcohol, and caffeine intake during pregnancy, maternal height and weight before pregnancy, years of school, occupational status, marital status, and number of antenatal care visits did not change the results. Adjustment for mother's age marginally reduced the risk of SIDS associated with smoking (OR = 3.0; 95% CI 1.2–7.3). CONCLUSIONS: Given the prospective nature of the study, the number of deaths is small; however, if our results reflect a true association between smoking during pregnancy and SIDS, approximately 30–40% of all cases of SIDS could be avoided if all pregnant women stopped smoking in a population with 30% pregnant smokers. Our study adds to earlier evidence for an association between smoking during pregnancy and SIDS. The strengths of the study are the possibility to adjust for a number of potential confounders and the fact that information about smoking habits during pregnancy was prospectively collected.